2006
DOI: 10.1007/s00126-006-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of fluid mixing in the formation of stratabound Pb–Zn–Ba–F mineralisation in the Alston Block, North Pennine Orefield (England)

Abstract: The North Pennine Orefield Alston Block has produced approximately 4 Mt Pb, 0.3 Mt Zn, 2.1 Mt fluorite, 1.5 Mt barite, 1Mt witherite plus a substantial amount of iron ore and copper ore from predominantly vein-hosted mineralisation in Carboniferous Limestones. However, a significant proportion of this production (c. 20 %) came from stratabound deposits. Though much is known about the vein-mineralisation, the relationship between the veins and the stratabound mineralisation is not well understood. New petrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 27 publications
3
16
0
Order By: Relevance
“…2008), and the metal enrichment has been related to fluid–rock interaction during basinal flow. In the North Pennines Orefield (Bouch et al. 2006), microchemical analyses of fluorite and quartz samples revealed higher levels of dissolved metals (Fe up to 7100 p.p.m., Zn up to 1130 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008), and the metal enrichment has been related to fluid–rock interaction during basinal flow. In the North Pennines Orefield (Bouch et al. 2006), microchemical analyses of fluorite and quartz samples revealed higher levels of dissolved metals (Fe up to 7100 p.p.m., Zn up to 1130 p.p.m.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing between fluoride‐rich metalliferous brines and low‐salinity surficial or connate brines has been accepted as the most important mineralizing process in other fluorite‐rich districts in Europe, such as in the North Pennine Orefield (Cann & Banks 2001; Bouch et al. 2006), the North German Basin (Lüders et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lead associated with barite in mineralized veins has been extensively reported in various deposits such as for the Mississippi Valley-type ore deposit found within carbonate rocks (35). This association may be attributed to coprecipitation of Pb-rich sulfides (galena) with the gangue minerals such as sulfates (barite, anhydrite) (36,37).…”
Section: Resultsmentioning
confidence: 88%
“…Nevertheless, the granites are now thought to provide a heat flux which would drive fluid movement [42]. There is no doubt that fluid flow was complex and has been demonstrated by Bouch et al [43] who identified earlier pervasive dolomitization and ankeritization, which took place in the presence of a high salinity brine, possibly one which was expelled from progressively maturing basinal shales over a period extending from the Late Carboniferous into the Early Permian. In summary, therefore, there is no convincing evidence from the orefield that the hydrothermal fluids were related to the metal enrichment in the coals, which is consistent with the present work where it is thought the enrichment was depositional.…”
Section: Discussionmentioning
confidence: 99%